The Role of Parents in the Character Formation of Adolescent - Gandha Metri, Gustiya (Journal Business Inovation, Accounting and Management, 2025)
This study aims to investigate the role of parents in shaping the character of adolescent children. Through a literature review, this research analyzes secondary data from various sources to understand how parents can foster strong and positive character in their adolescent children. The findings of this study indicate that parents who adopt positive parenting styles, are actively involved in their children's lives, and maintain effective communication with their children tend to raise adolescent children with strong and positive character. This study concludes that the role of parents is crucial in shaping the character of adolescent children and recommends that parents adopt positive parenting styles, be actively involved in their children's lives, and maintain effective communication with their children to foster strong and positive character in their adolescent children. This study has significant implications for parents, educators, and practitioners working with adolescent children to understand the role of parents in shaping the character of adolescent children and to work together to foster strong and positive character in adolescent children. By understanding the importance of parental involvement and positive parenting practices, parents and educators can collaborate to provide adolescent children with the support and guidance they need to develop strong and positive character, ultimately leading to better outcomes in their personal and social lives.